2014
DOI: 10.1007/s00216-014-8069-0
|View full text |Cite
|
Sign up to set email alerts
|

Relating surface-enhanced Raman scattering signals of cells to gold nanoparticle aggregation as determined by LA-ICP-MS micromapping

Abstract: The cellular response to nanoparticle exposure is essential in various contexts, especially in nanotoxicity and nanomedicine. Here, 14-nm gold nanoparticles in 3T3 fibroblast cells are investigated in a series of pulse-chase experiments with a 30-min incubation pulse and chase times ranging from 15 min to 48 h. The gold nanoparticles and their aggregates are quantified inside the cellular ultrastructure by laser ablation inductively coupled plasma mass spectrometry micromapping and evaluated regarding the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 61 publications
3
72
1
2
Order By: Relevance
“…[173] Moreover,a ggregates were formed within the cells,w hich were being responsible for strong SERS signals during mapping.Asafurther approach, the complex assembly of nanoparticles and nanorods was illustrated based on the selective modification of nanorods with DNAo ligomers. When AuNPs were taken up by cells,t he SERS spectra indicated that the nanoparticle surface was coated mainly by proteins.…”
Section: Label-free Sers Detection Of Cells and Tissuesmentioning
confidence: 99%
“…[173] Moreover,a ggregates were formed within the cells,w hich were being responsible for strong SERS signals during mapping.Asafurther approach, the complex assembly of nanoparticles and nanorods was illustrated based on the selective modification of nanorods with DNAo ligomers. When AuNPs were taken up by cells,t he SERS spectra indicated that the nanoparticle surface was coated mainly by proteins.…”
Section: Label-free Sers Detection Of Cells and Tissuesmentioning
confidence: 99%
“…[25,26] In this respect, different types of SERS-substrates have been developed to obtain plasmon enhancement and record Raman spectra from (sub)cellular components down to the single biomolecule level. [27] These can be, but are not limited to, well defined nanostructured surfaces of gold [28] or silver [29] and (intracellular) aggregated Ag [30] or AuNP [31] . Both Ag-nanograin coated chips and precipitated AuNP clusters were recently applied for bulk EV measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of ICP-MS such as single nanoparticle ICP-MS are available that allow some quantification of individual NPs [10]. Other modifications such as laser-ablation-ICP-MS allow imaging of the sub-cellular localization of NPs with a μm-resolution [11]. …”
Section: Introductionmentioning
confidence: 99%